2002
DOI: 10.1139/w02-052
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of mixtures of yeast and potato extracts in growth media for biomass production of lactic cultures

Abstract: The effectiveness of yeast extracts (YE) and potato extracts (PE) to promote growth of seven lactic cultures was evaluated by automated spectrophotometry (AS). Two aspects of the growth curve were analysed: (1) maximum biomass obtained (using ODmax) and (2) highest specific growth rate mu(max)) Eleven lots from the same PE-manufacturing process were examined for lot-to-lot variability. The ODmax values of three of the seven strains were significantly affected by lot source, but mu(max) was not significantly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…[9][10][11] Hence several studies have been carried out to replace expensive nitrogen sources with ingredients at low cost such as food by-products or agricultural wastes. With this aim, whey and buttermilk, 12) de-lipidated egg yolk and yeast autolysate, 9) fish viscera, 8) cassava bagasse and sugarcane bagasse, 13) spent cabbage juice, 14) a mixture of yeast and potato extracts, 15) juice of pineapple peel, 16) and corn steep liquor 17) have been tested. The growth and functionality of Lactobacillus in the tested products were compared to that in standard lactobacilli MRS.…”
mentioning
confidence: 99%
“…[9][10][11] Hence several studies have been carried out to replace expensive nitrogen sources with ingredients at low cost such as food by-products or agricultural wastes. With this aim, whey and buttermilk, 12) de-lipidated egg yolk and yeast autolysate, 9) fish viscera, 8) cassava bagasse and sugarcane bagasse, 13) spent cabbage juice, 14) a mixture of yeast and potato extracts, 15) juice of pineapple peel, 16) and corn steep liquor 17) have been tested. The growth and functionality of Lactobacillus in the tested products were compared to that in standard lactobacilli MRS.…”
mentioning
confidence: 99%
“…However, other inexpensive nutrients can be used as ingredients of the fermentation medium, which could further reduce the cost of production. Several studies have replaced the expensive MRS medium for lactobacilli with supplemented whey permeate [11,32] or several carbon and nitrogen sources of vegetal origin, such as potato extracts [13], molasses, soy milk [34] and corn syrup [12]. Continuous control of pH has also been used to improve the growth and metabolite production of LAB [11,32].…”
Section: Discussionmentioning
confidence: 99%
“…The optimum point medium investigated by Oh et al was found to be approximately twice more productive than the center-point medium, and more economical than the MRS medium [5]. The maximum biomass for L. casei EQ28, L. rhamnosus R-011, L. plantarum EQ12, and Streptococcus thermophilus R-083 was also obtained with a mixture of yeast and potato extracts [8]. Thus, through partial replacement of yeast extract with the less expensive 40 % potato extract, strong economical advantages could be observed.…”
Section: V) Validating the Optimum Points Of The Factorsmentioning
confidence: 99%
“…The effectiveness of yeast extracts and potato extracts has been evaluated to promote the growth of lactic acid bacteria (LAB) such as L. casei EQ28, L. rhamnosus R-011, L. plantarum EQ12 and Streptococcus thermophilus R-083 by automated spectrophotometry [8]. The growth kinetics of several LAB (L. fermentum, L. reuteri, L. acidophilus and L. plantarum) that have potential to be used as probiotics in cereal-based substrates such as wheat, barley and malt have been reported [9].…”
mentioning
confidence: 99%